2006
DOI: 10.2353/ajpath.2006.050500
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective and Blood-Retinal Barrier-Preserving Effects of Cannabidiol in Experimental Diabetes

Abstract: Diabetic retinopathy is characterized by blood-retinal barrier (BRB) breakdown and neurotoxicity. These pathologies have been associated with oxidative stress and proinflammatory cytokines, which may operate by activating their downstream target p38 MAP kinase. In the present study, the protective effects of a nonpsychotropic cannabinoid, cannabidiol (CBD), were examined in streptozotocin-induced diabetic rats after 1, 2, or 4 weeks. Retinal cell death was determined by terminal dUTP nick-end labeling assay; B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
173
2
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 234 publications
(203 citation statements)
references
References 58 publications
(113 reference statements)
24
173
2
4
Order By: Relevance
“…Research demonstrating increased levels of the peroxynitrite biomarker nitrotyrosine in retinas of diabetic patients and experimental animal models supports this concept and implies a role for peroxynitrite in the development of diabetic complications (Abu El-Asrar et al, 2004;Du et al, 2002;ElRemessy, 2003b;Kowluru and Odenbach, 2004;Obrosova et al, 2005). Studies in animal and tissue culture models have demonstrated that increased peroxynitrite formation is directly correlated with diabetes, high glucose-induced VEGF expression, and increased retinal vascular permeability (El-Remessy, 2003a;El-Remessy, 2003b;El-Remessy et al, 2006;El-Remessy et al, 2005). This cycle can be interrupted by treatments that reduce superoxide or peroxynitrite levels or inhibit NOS activity.…”
Section: Oxidative Stress and Diabetic Retinopathymentioning
confidence: 96%
See 1 more Smart Citation
“…Research demonstrating increased levels of the peroxynitrite biomarker nitrotyrosine in retinas of diabetic patients and experimental animal models supports this concept and implies a role for peroxynitrite in the development of diabetic complications (Abu El-Asrar et al, 2004;Du et al, 2002;ElRemessy, 2003b;Kowluru and Odenbach, 2004;Obrosova et al, 2005). Studies in animal and tissue culture models have demonstrated that increased peroxynitrite formation is directly correlated with diabetes, high glucose-induced VEGF expression, and increased retinal vascular permeability (El-Remessy, 2003a;El-Remessy, 2003b;El-Remessy et al, 2006;El-Remessy et al, 2005). This cycle can be interrupted by treatments that reduce superoxide or peroxynitrite levels or inhibit NOS activity.…”
Section: Oxidative Stress and Diabetic Retinopathymentioning
confidence: 96%
“…Moreover, exogenous peroxynitrite increases VEGF expression in cultured RECs (Platt et al, 2005). Increases in retinal nitrotyrosine levels and lipid peroxidation have been shown to correlate with VEGF overexpression and breakdown of the blood-retinal barrier, and treatments that reduce peroxynitrite formation have been shown to block the early signs of diabetic retinopathy (El-Remessy, 2003b;El-Remessy et al, 2006). Moreover, VEGF itself has been shown to promote the formation of superoxide anion and peroxynitrite in cultured endothelial cells (El-Remessy et al, 2007;Ushio-Fukai et al, 2002).…”
Section: 74mentioning
confidence: 99%
“…Blood-retinal barrier function Integrity of the BRB was measured as previously described by our group [3,12]. Plasma was assayed for fluoresciene concentration using a plate reader (excitation 370 nm, emission 460 nm) (BioTek).…”
Section: Methodsmentioning
confidence: 99%
“…These changes lead to accelerated cell death within the inner retinal and ganglion cells [1][2][3] and blood-retinal barrier (BRB) breakdown resulting in macular oedema and neovascularisation [4]. Clinically, the disease manifests as diabetic retinopathy and eventually leads to impaired vision.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation